Clinical and radiographic evaluation of new dental implant system: Results of a 3-year prospective study - Seçil Karakoca Nemli; Merve Bankoğlu Güngör; Cemal Aydın; Handan Yılmaz; Bilge Turhan Bal; Yeliz Kaşko Arıcı (Elsevier, 2016)
Background/purpose: The aim of this study was to evaluate implant survival, crestal bone level changes, and clinical parameters of IDcam dental implants over a mean follow-up period of 3 years. Materials and methods: Seventy-two patients, 32 females and 40 males, received 255 implants. Implant-supported metal-ceramic fixed restorations were inserted. Following completion of restorations, each patient was re-examined at 6-month intervals. Radiographic crestal bone level changes were calculated, as well as soft tissue parameters including pocket probing depth, bleeding on probing, plaque index, and gingival index. Examination results were recorded from 18 months to 42 months. Implant survival was estimated using the Kaplan-Meier method. Associations between implant survival and recorded variables were estimated using Cox proportional regression analysis. Results: The Kaplan-Meier survival analysis demonstrated a cumulative survival rate of 97.6%. Three implants in three patients failed to osseointegrate at stage 2 surgery, and three implants in three patients were lost after loading. The mean marginal bone losses were 0.35 ± 0.14 mm, 0.47 ± 0.15 mm, and 0.58 ± 0.16 mm, as determined 6 months, 12 months, and 24 months after prosthetic loading, respectively. Cox proportional regression analysis revealed that the variables such as age, sex, type of the restoration, and implant region had no significant influence on implant failure (P > 0.05). Coefficients of correlation between implant survival and crestal bone loss, pocket probing depth, bleeding on probing, plaque index, and gingival index were found to be nonsignificant (P > 0.05). Conclusion: Survival and radiographic and clinical assessments of implants after 2 years of function demonstrated promising results for an IDcam dental implant system.